Aneurysms in Vascular Access: State of the Art and Future Developments. Issue 6 (November 2017) - Inston, Nicholas; Mistry, Hiren; Gilbert, James; Kingsmore, David; Raza, Zahid; Tozzi, Matteo; Azizzadeh, Ali; Jones, Robert; Deane, Colin; Wilkins, Jason; Davidson, Ingemar; Ross, John; et al.
A master class was held at the Vascular Access at Charing Cross (VA@CX2017) conference in April 2017 with invited experts and active audience participation to discuss arteriovenous (AV) vascular access aneurysms, a serious and common complication of vascular access (VA). The natural history of aneurysms in VA is poorly defined, and although classifications exist they are not uniformly applied in studies or clinical practice. True and pseudo aneurysms of AV access occur. Whilst an AV fistula by definition is an abnormal dilatation of a blood vessel, an agreed definition of 18 mm, or 3 times accepted maturation diameter, is proposed. The mechanism of aneurysmal dilatation is unknown but appears to be a combination of excessive external remodeling, wall changes due to injury, and obstruction of outflow. Diagnosis of AV aneurysms is based on physical examination and ultrasound. Venography and cross-sectional imaging may assist and be required for the investigation of outflow stenosis. Treatment of pseudo aneurysms and true aneurysms of VA (AVA) is not evidence-based, but relies on clinical experience and available facilities. In many AVA, a conservative approach with surveillance is suitable, although intervals and modalities are unclear. Avoidance of rupture is imperative and preemptive treatment should aim for access preservation, ideally with avoidance of prosthetic materials. Different techniques of aneurysmorrhaphy are described with good results in published series. Although endovascular approaches and stenting are described with good short-term results, issues with cannulation of stented areas occur and, while possible, this is not recommended, and long-term access revision is recommended.